The Linguistic Shaping of Landscape Painting Styles by Traditional Philosophies - Zhou, Wei; Zhang, Yongkang (Forum for Linguistic Studies, 2025)
Beginning with the relationship between traditional philosophy and landscape painting styles, this study systematically demonstrates how the three major philosophical traditions—Taoism, Confucianism, and Buddhism—have shaped the artistic language of landscape painting. The research finds that traditional philosophy primarily influences landscape painting styles through three dimensions: compositional language, brush-ink language, and conceptual language. In compositional language, the shaping is achieved through two core mechanisms: “the interplay between emptiness and solidity” and “the unity of heaven and humanity,” where Taoist yin-yang dialectical thinking dominated the treatment of empty-solid relationships, while Confucian unity of heaven and humanity influenced the overall composition; in brush-ink language, this is reflected in two aspects: “simplified and implicit” brushwork characteristics and profound ink-wash artistic conception, with Taoist “quiet non-action” thought directly influencing the artistic pursuit of “one stroke serving as ten”; in conceptual language, influence is primarily generated through the handling of subject-object relationships and the pursuit of transcendent realms. This shaping mechanism, characterized by its multi-layered and systematic nature, has not only influenced artistic creation itself but also had inevitable impacts on art and cultural inheritance. In the context of contemporary artistic creation, this shaping mechanism still holds significant inspirational value, providing important intellectual resources for addressing the relationships between tradition and innovation, and between local and international perspectives.